2011
DOI: 10.1016/j.memsci.2011.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Direct contact membrane distillation (DCMD): Experimental study on the commercial PTFE membrane and modeling

Abstract: Membrane distillation (MD) is an alternative technology for the separation of mixtures through porous hydrophobic membranes. A commercially available PTFE (Polytetrafluoroethylene) membrane was used in Direct Contact Membrane Distillation (DCMD) to investigate the effect of module dimensions on performance. Membrane properties, such as liquid entry pressure (LEP), contact angle (CA), pore diameter, effective porosity and pore size distribution, were characterized and used in analysis. A two dimensional (2D) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
92
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(97 citation statements)
references
References 21 publications
5
92
0
Order By: Relevance
“…Contact angle values of water on some materials at ambient temperature (Khayet & Matsuura, 2011;Sigurdsson & Shishoo, 1997) different materials in water at ambient temperature. For example, the parameter measured on PTFE or PVDF membrane surface was 108° or 107°, respectively (Curcio et al, 2010;Hwang et al, 2011;Tomaszewska, 2000).…”
Section: Contact Anglementioning
confidence: 99%
“…Contact angle values of water on some materials at ambient temperature (Khayet & Matsuura, 2011;Sigurdsson & Shishoo, 1997) different materials in water at ambient temperature. For example, the parameter measured on PTFE or PVDF membrane surface was 108° or 107°, respectively (Curcio et al, 2010;Hwang et al, 2011;Tomaszewska, 2000).…”
Section: Contact Anglementioning
confidence: 99%
“…For instance, in a membrane-based ventilator system [34,35], the mass and heat transfer through a membrane and two fluids was treated as a conjugate problem by ignoring phase changes. In a study of an MD system [36], the feed, permeate and membrane were incorporated into the simulation to obtain velocity and temperature fields, but the concentration transport and latent heat induced by evaporation were ignored. Another CFD study of MD flat sheet membrane module design suggested that spacer orientations should have great impact on the heat and mass transfer [37].…”
Section: Introductionmentioning
confidence: 99%
“…However, the heat-transfer model developed in this study was over-simplified being based on non-porous and rigid shell and tube heat exchangers, which are not coupled with the mass transfer and phase changes. Moreover, these prior simulation studies only focused on mass-and/or heat-transfer improvement by designing better flow channels or incorporating spacers for both non-MD and MD flat sheet or spiral wound membrane modules [37][38][39][40][41][42]. Thus far, CFD analysis for process modeling in hollow fiber MD modules has been limited to our previous work [33,43].…”
Section: Introductionmentioning
confidence: 99%
“…The driven force in this technique is the partial vapor pressure difference on both sides of the membrane, directly linked to the process temperature (Rivier et al, 2002). The vapor passing through the membrane (permeate) can be assured in several ways: Direct Contact Membrane Distillation (DCMD) (Cerneaux et al, 2009;Hwang et al, 2011;Khayet, Mengual & Matsuura, 2005), Air Gap Membrane Distillation (AGMD) (Alkhudhiri, Darwish & Hilal, 2012), Vacuum Membrane Distillation (VMD) (Cerneaux et al, 2009) or using Sweeping Gas Membrane Distillation (SGMD) (Cojocaru & Khayet, 2011). From these configurations, VMD and SGMD are the ones having the largest industrial potential application, due to an easier recovery implementation principle (vacuum and sweep gas).…”
Section: Introductionmentioning
confidence: 99%